Appraisal and coping predict health and well‐being during the COVID‐19 pandemic: An international approach. (29th June 2021) - Kirby, Leslie D.; Qian, Weiqiang; Adiguzel, Zafer; Afshar Jahanshahi, Asghar; Bakracheva, Margarita; Orejarena Ballestas, María C.; Cruz, José Fernando A.; Dash, Arobindu; Dias, Claudia; Ferreira, Maria J.; Goosen, Johanna G.; Kamble, Shanmukh V.; et al.
Abstract : COVID‐19 has had a devastating impact on people worldwide. We conducted an international survey ( n = 3646) examining the degree to which people's appraisals and coping activities around the pandemic predicted their health and well‐being. We obtained subsamples from 12 countries—Bangladesh, Bulgaria, China, Colombia, India, Israel, the Netherlands, Norway, Peru, Portugal, Turkey and the United States. For each, we assessed appraisals and coping strategies as well as indicators of physical and mental health and well‐being. Results indicated that, despite mean‐level societal differences in outcomes, the pattern of appraisals and coping strategies predicting health and well‐being was consistent across countries. Use of disengagement coping (particularly behavioural disengagement and self‐isolation) was associated with relatively negative outcomes. In contrast, optimistic appraisals (particularly of high accommodation‐focused coping potential and the ability to meet one's physical needs), use of problem‐focused coping strategies (especially problem‐solving) and accommodative coping strategies (especially positive reappraisal and self‐encouragement) were associated with relatively positive outcomes. Our study highlights the critical importance of considering accommodative coping in stress and coping research. It also provides important information on how people have been dealing with the pandemic, the predictors of well‐being under pandemic conditions and the generality of such relations.